The persistence length of linear surfactants modulates the self-assembly of reverse micelles and their diffusion in nonpolar solvents - Hernández Velázquez, J. D; Santos-Santos, J; Gama Goicochea, A (Molecular systems design & engineering, 2022)
The self-assembly of linear model surfactants into reverse micelles (RMs) in a nonpolar solvent is studied here for two surfactant lengths, through numerical simulations. The study was carried out at a fixed 1 : 1 water/surfactant ratio, finding that the self-diffusion of RMs depends on the persistence length of the individual HT (head-tail) surfactants. Additionally, it is found that the number of RMs formed depends on the conjunction of two parameters: the persistence length and the polymerization degree of the HT surfactant. The role played by the persistence length of the surfactants in RM formation is found to be that stiffer surfactants tend to form a fewer number of RMs, with low diffusion. Such results can provide useful insights for industrial or pharmacological applications where RMs are involved, since the very modification of the persistence length can enhance their utility as drug carriers or thickeners. The self-assembly of linear model surfactants into reverse micelles (RMs) in a nonpolar solvent is studied here for two surfactant lengths, through numerical simulations.